Inhibitory Effect of Selenium Nanoparticles on the Biofilm Formation of Multidrug-Resistant Acinetobacter Baumannii - Šmitran, Aleksandra; Luković, Bojana; Božić, Ljiljana; Golić, Bojan; Gajić, Ina (Scripta Medica, 2024)
Background/Aim: Treatment of infections caused by biofilm-producing multidrug-resistant (MDR) pathogens represents a huge global problem due to primary antimicrobial multi-resistance enhanced by reduced penetration of antibiotics in the biofilm-embedded bacteria. The aim of this study was to determine the capacity of biofilm production among MDR Acinetobacter baumannii (A baumannii) isolates obtained from different clinical specimens and to evaluate the inhibitory effect of selenium nanoparticles (SeNPs) coated with cationic polymer cetyltrimethylammonium bromide (CTAB) on the biofilm formation. Methods: Antimicrobial effect of antibiotics (meropenem, imipenem, gentamicin, amikacin, ciprofloxacin, levofloxacin and trimethoprim-sulfamethoxazole) was determined by disk-diffusion assay, while sensitivity to colistin was determined with E test. All 60 isolates were tested on biofilm production in microtiter plates with crystal violet dye. Minimal biofilm inhibitory concentration (MBIC) of SeNPs was tested in order to prevent biofilm formation in microtiter plates. Results: All tested clinical isolates were classified as MDR (n = 60) and extensively drug-resistant (XDR, n = 60). Out of the total 60 isolates, 55 isolates (92 %) showed the ability for biofilm formation, with the majority of them classified as strong (42 %) and moderate (42 %) biofilm producers. MBIC values of SeNPs for 55 biofilm-producing isolates ranged from 0.07 to 1.25 mg/mL. Strong biofilm producers had statistically higher MBIC (0.15 mg/mL) in correlation to other biofilm-producing isolates (0.07 mg/mL). There was no correlation between invasiveness of isolates with biofilm production and MBIC values. Conclusion: Presented results are very promising and interesting especially in nanotechnology and medical fields, while SeNPs with the addition of cationic surfactant inhibit biofilm formation of MDR A baumannii clinical isolates.